A SUGGESTED PROGRAM FOR COLLEGE TRAINING IN ACCOUNTANCY. - Boyd, Ralph L. (The Accounting Review, 1946)
Abstract Accounting is essentially a technical subject. It accumulates, verifies, presents and interprets financial information about operations and properties for business enterprise or about financial activities and resources for government and nonprofit organizations. It deals also with the means and methods of controlling the receipt, possession and disposition of properties to establish personal responsibility, to reduce the possibility of errors and to minimize the opportunity for fraud. Certain phases of accounting study give the student some knowledge of business operations, of the importance of the profit system in an economic society, and of the need for financial information by management, owners, creditors, government, employees and the general public. Accounting courses too frequently do not meet the needs for social, personal and supplementary training in accounting. These needs cannot adequately be met by the content of the usual elementary accounting courses. Not all students can be, nor should they be, fitted into an all-purpose curriculum. Provision should be made for one or more accounting courses especially designed for these purposes.